A new framework for understanding stress and disease: the developmental model of stress as applied to multiple sclerosis - Fauver, Michelle; Clark, Eva M.; Schwartz, Carolyn E. (Frontiers in Integrative Neuroscience, 2024)
Ethics approval. The protocol was reviewed and approved by the California Institute for Human Science Institutional Review Board.Consent for publication. All participants provided full consent.Availability of data and material. The data used in the content analyses are confidential and thus not able to be shared. Data for the pilot study are available for review.Conflicts of interest/Competing interest. All authors declare that they have no potential conflicts of interest and report no disclosures.